Cancer risk‐reducing surgery: Brazilian Society of Surgical Oncology Guideline Part 2 (Gastrointestinal and thyroid). Issue 1 (11th June 2022) - Carneiro, Vandré C. G.; Gifoni, Ana C. L. V. C.; Rossi, Benedito M.; da Cunha Andrade, Carlos E. M.; de Lima, Fernanda T.; de Campos Reis Galvão, Henrique; da Rocha, Jose C. C.; da Silva Barreto, Leonardo S.; Ashton‐Prolla, Patrícia; Guindalini, Rodrigo S. C.; de Farias, Terence P.; Andrade, Wesley P.; et al.
Abstract: Background: Risk‐reducing operations are an important part of the management of hereditary predisposition to cancer. In selected cases, they can considerably reduce the morbidity and mortality associated with cancer in this population. Objectives: The Brazilian Society of Surgical Oncology (BSSO) developed this guideline to establish national benchmarks for cancer risk‐reducing operations. Methods: The guideline was prepared from May to December 2021 by a multidisciplinary team of experts to discuss the surgical management of cancer predisposition syndromes. Eleven questions were defined and assigned to expert groups that reviewed the literature and drafted preliminary recommendations. Following a review by the coordinators and a second review by all participants, the groups made final adjustments, classified the level of evidence, and voted on the recommendations. Results: For all questions including risk‐reducing colectomy, gastrectomy, and thyroidectomy, a major agreement was achieved by the participants, always using accessible alternatives. Conclusion: This and its accompanying article represent the first guideline in cancer risk reduction surgery developed by the BSSO and it should serve as an important reference for the management of families with cancer predisposition.